2009
DOI: 10.1007/s00449-009-0380-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of human granulocyte-colony stimulating factor production in recombinant E. coli using batch cultivation

Abstract: Development of inexpensive and simple culture media is always favorable for recombinant protein over-expression in E. coli. The effects of medium composition on the production of recombinant human granulocyte-colony stimulating factor (rh-GCSF) were investigated in batch culture of E. coli BL21 (DE3) [pET23a-hgcsf]. First, the optimum medium for production of rh-GCSF was determined; and, then it was shown that mixture of amino acid addition at induction time, which was determined on the basis of amino acids fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Most commonly, induction is carried out during the exponential growth phase when cells are most actively dividing and when the protein expression machinery is believed to be the most active [18,21,22,36]. In contrast, our studies indicated that maximum SELP volumetric productivity is achieved by induction at the beginning of the stationary phase (8 hrs.…”
Section: Resultsmentioning
confidence: 66%
“…Most commonly, induction is carried out during the exponential growth phase when cells are most actively dividing and when the protein expression machinery is believed to be the most active [18,21,22,36]. In contrast, our studies indicated that maximum SELP volumetric productivity is achieved by induction at the beginning of the stationary phase (8 hrs.…”
Section: Resultsmentioning
confidence: 66%
“…On the other hand, the production of the recombinant protein referred to as inclusion body has not only disadvantages, but also has some advantages. 15,18 The primary advantage is the ease of purification of IBs and it contains high degree purity of target protein.…”
Section: 14mentioning
confidence: 99%
“…Efficient cell lysis and maximum protein extraction yields are vital to high‐quality recombinant protein purification. Mechanical lysis by high‐pressure homogenization or sonication or lysis by freeze–thaw procedures with lysozyme is equivalent in most cases [18,19]. After the appropriate cell disruption, IBs are easily separated by high‐speed centrifugation.…”
Section: Introductionmentioning
confidence: 99%
“…After the appropriate cell disruption, IBs are easily separated by high‐speed centrifugation. Further purification of IBs can be achieved by washing them with detergents, low concentration of salt, and or urea as the best approach [18,20]. With proper isolation and washing processes, IBs with a purity of more than 95% can be obtained from E. coli [21].…”
Section: Introductionmentioning
confidence: 99%